2018
DOI: 10.1016/j.renene.2017.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-physical properties of nanoparticle-seeded nitrate molten salts

Abstract: Highlights  Three types of nanoparticle were dispersed into two different types of solar salts.  Nanosalts show enhanced thermal diffusivity/conductivity, sensible heat and latent heat.  0.5 wt. % Fe 2 O 3-nanosalt increased thermal diffusivity of solar salt up to 50%.  14.5 % enhancement of the latent heat of solar salt was found for KNO 3.  5.3 % enhancement of the total storage capacity was found at 155 ºC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 112 publications
(47 citation statements)
references
References 33 publications
4
43
0
Order By: Relevance
“…At high concentrations, the abnormal results obtained indicate that the samples are not stable and the agglomeration of nanoparticles leads to a change in the nanofluid composition and properties on the measurement spot thus providing thermal conductivities even lower than the pure salt. The same trend with solid content and temperature can be found in [23]. where  is the volume fraction of nanoparticles and knf, knp and kbf are the thermal conductivities of the nanofluid, nanoparticle and base fluid respectively.…”
Section: Thermal Conductivity and Heat Transfersupporting
confidence: 66%
See 1 more Smart Citation
“…At high concentrations, the abnormal results obtained indicate that the samples are not stable and the agglomeration of nanoparticles leads to a change in the nanofluid composition and properties on the measurement spot thus providing thermal conductivities even lower than the pure salt. The same trend with solid content and temperature can be found in [23]. where  is the volume fraction of nanoparticles and knf, knp and kbf are the thermal conductivities of the nanofluid, nanoparticle and base fluid respectively.…”
Section: Thermal Conductivity and Heat Transfersupporting
confidence: 66%
“…The addition of nanoparticles to a base fluid implies an increment in the thermal conductivity of the nanofluid due to the higher thermal conductivity of the solid. Furthermore, although according to the mixture rule the specific heat of the nanofluid should decrease due to the lower specific heat of the nanoparticles, abnormal enhancements in the specific heat capacity of molten salts and ionic liquids have been reported [14][15][16][17][18][19][20][21][22][23][24][25][26]. This enhancement provides an increase in the sensible heat storage capacity of the TES material thus improving the efficiency of the storage system.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the distributions of the nanoparticle sizes were measured with a Malvern Nanosizer (Malvern Instruments Limited, Malvern, UK), which was based on dynamic light scatting (DLS) method according to the hydrodynamic diameter of nanoparticles. The method of the preparation of nanofluids was the same as that of Award et al [39], Al 2 O 3 nanopowder and graphene were dispersed in distilled water with a concentration of about 0.1%, then the nanofluids without any surfactant for stability were sonicated for about 2 h. The number of nanoparticles of each diameter were determined subsequently after the measurements. The modal distribution named intensity of nanoparticles were obtained as the measurements were repeated three times for each sample.…”
Section: Characterization Of Nanocomposites and Nanoparticlesmentioning
confidence: 99%
“…[15][16][17][18] Shin and Banerjee 19 doped SiO 2 nanoparticles into carbonate salt and obtained enhancement of 5-15% and 25-28% for specific heat and thermal diffusivity, respectively. Awad et al 20 investigated the thermophysical properties of nitrate salt with various nanoparticles. And they found that the thermal diffusivity and the total energy storage were enhanced by 50% and 6%, respectively.…”
Section: Introductionmentioning
confidence: 99%